Locating Underground Water Pipe Leakages Via Interpretation of Ground Penetrating Radar Signals - F. Senin, S.; S. Jaafar, M.; Hamid, R. (International Journal of Engineering and Technology, 2019)
Water wastage due to leakages in the water distribution system is a common problem encountered worldwide. The detection and localization of water pipes’ leakages in the underground pipe system is possible by the high-resolution images of Ground Penetrating Radar (GPR) with 1.6 GHz antenna. Experimental simulation of water leakage for shallow buried PVC pipe at a depth of 0.24 m and 0.23 m in mediums of dry sand and loose soil, respectively was performed. Holes were drilled in the middle of the pipe to allow water to leak inside the soils. The presence of water in the soils is detected as the soils’ moistures influence the GPR signal reflection characteristics. The GPR images show appearance of delayed hyperbolas and the attenuation of reflection when the water content increased. The increased in dielectric constant and the reduction of wave velocity of the GPR signals in soil enabled the inspector to detect the water leakage in pipes. Results showed that the depth of the water leakages in the pipes were detected at 0.242 m 0.220 m respectively. GPR method is able to locate the underground water pipes leakages in the underground pipes accurately.